2012
DOI: 10.1088/1748-9326/7/2/024003
|View full text |Cite
|
Sign up to set email alerts
|

Variability and trends of aerosol properties over Kanpur, northern India using AERONET data (2001–10)

Abstract: Natural and anthropogenic aerosols over northern India play an important role in influencing the regional radiation budget, causing climate implications to the overall hydrological cycle of South Asia. In the context of regional climate change and air quality, we discuss aerosol loading variability and trends at Kanpur AERONET station located in the central part of the Indo-Gangetic plains (IGP), during the last decade (2001-10). Ground-based radiometric measurements show an overall increase in column-integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(67 citation statements)
references
References 39 publications
5
56
2
2
Order By: Relevance
“…Srivastava [39] found that the positive trends in AOD are found over the main continental regions of South Asia based on ground-based radiometric measurements. Kaskaoutis, et al [40] exhibited overall increasing trends in AOD (7.69%) with a high significance based on Aerosol Robotic Network (AERONET) measurements from 2001 to 2010 in northern India, which are consistent with satellite observations (MODIS) of increasing AOD and enhanced anthropogenic emissions over India. Moreover, Bibi, et al [41] also reported a high degree of correlation (above 0.7) between the inter-comparison of MODIS AOD and AERONET data in India.…”
Section: Of 17supporting
confidence: 60%
See 1 more Smart Citation
“…Srivastava [39] found that the positive trends in AOD are found over the main continental regions of South Asia based on ground-based radiometric measurements. Kaskaoutis, et al [40] exhibited overall increasing trends in AOD (7.69%) with a high significance based on Aerosol Robotic Network (AERONET) measurements from 2001 to 2010 in northern India, which are consistent with satellite observations (MODIS) of increasing AOD and enhanced anthropogenic emissions over India. Moreover, Bibi, et al [41] also reported a high degree of correlation (above 0.7) between the inter-comparison of MODIS AOD and AERONET data in India.…”
Section: Of 17supporting
confidence: 60%
“…This result is has important contributions from the extensive cloud contamination on MODIS during the monsoon season [33]. Additionally, the consistently robust and rapid increase in aerosols in South Asia have verified by satellite and ground-based observations from many previous studies [38][39][40]. Srivastava [39] found that the positive trends in AOD are found over the main continental regions of South Asia based on ground-based radiometric measurements.…”
Section: Of 17supporting
confidence: 59%
“…Satellite data needs validation using ground based measurements Kahn et al, 2005;Remer et al, 2005). Recently, ground-based AERONET Kaskaoutis et al, 2012b) and satellite data (Polarization and Directionality of the Earth's Reflectances, POLDER; Total Ozone Mapping Spectrometer, TOMS; MODIS; and MISR) have been used extensively to study the variability of aerosol optical properties over the Indo-Gangetic basin (Goloub et al, 2001;Di Girolamo et al, 2004;Massie et al, 2004;Singh et al, 2004;Prasad et al, 2004;Ramanathan and Ramana, 2005;Prasad et al, 2006;Tiwari et al, 2009;Dey and Girolamo, 2010;Srivastava et al, 2011;Kumar et al, 2012) which is one of the highly polluted regions of the world. Tripathi et al (2005) carried out MODIS AOD validation using 11 months data of level 2 MODIS for the year 2004; whereas Jethva et al (2005) have used 22 months of level 3 MODIS data for the periods (2001)(2002)(2003).…”
Section: Introductionmentioning
confidence: 99%
“…The construction activities throughout the region as well as the proximity (~15 km) with the Dadri power plant may also contribute to the high AODs over Greater Noida, while the influence of the local traffic and vehicular emissions is expected to be much lower than that over other urban Indian environments. The mean AOD is higher than those reported over Kanpur Eck et al, 2010;Giles et al, 2011;Kaskaoutis et al, 2012) and Gandhi College (Srivastava et al, 2011(Srivastava et al, , 2012, which are considered as highly polluted regions in IGP as well as than those reported over several Indian cities . Values of AOD at the level of ~0.8 were reported for Delhi (Singh et al, 2005 and during specific events of dust storms Badarinath et al, 2010 and/or biomass burning (Kharol et al, 2012) over IGP region.…”
Section: Severe Aerosol Loading Over Greater Noidamentioning
confidence: 52%
“…The large variability indicates significantly seasonal or even daily-changed atmospheric conditions and dominance of aerosol of different size, composition and optical properties. High values of α are observed during post-monsoon and winter seasons accompanied with low values during late pre-monsoon and monsoon seasons due to influence of dust, following the usual scenario over IGP (Soni et al, 2011;Kaskaoutis et al, 2012;Lodhi et al, 2013). The mean value of α 440-870 was found to be 0.95 ± 0.37, comparable to the yearly mean values that observed over other sites in IGP, like Delhi , Kanpur Kaskaoutis et al, 2012), and far East to Dibrugarh (Gogoi et al, 2009).…”
Section: Severe Aerosol Loading Over Greater Noidamentioning
confidence: 80%